Ecosystem provision services provided by agroecosystems of family gardens in the State of Mexico - Arcos Severo, Minerva; Gutiérrez Cedillo, Jesús Gastón; Balderas Plata, Miguel Ángel; Martínez García, Carlos Galdino (Revista de Biología Tropical, 2021)
Introduction: Provisioning ecosystem services (ES) provided by agroecosystems of family orchards (AEFO) refer to the tangible benefits that people obtain from the ecosystem. Although AEFO have been widely studied, few studies show their approach from an integral perspective, which incorporates biophysical and economic characteristics at the same time. Objective: To carry out an integral analysis of provisioning ecosystem services provided by agroecosystems of family orchards from State of Mexico. Methods: Information about provisioning ecosystem services (identification, uses, destination and income generation) were collected between March to December 2019 from three rural communities by involving 42 families with a family orchard using semi-structured interviews, questionnaires, species inventories, direct observation and field trips. Results: A sum of six provisioning ecosystem services were identified, which were associated to 212 species, distributed in 172 genera and 82 families. The main uses that the owners of the orchards gave to provisioning ES were ornamental (51 %), followed by food (39 %) and medicinal (32 %), where species such as Cymbopogon citratus, Persea americana, Punica granatum, Zea mays e Inga jinicuil, had the highest use values (U. V. = 4). The destination of the production was self-consumption, sale and exchange, being the first the main survival strategy used by households. Sale of edible products in fresh, as well as their derivatives, represented an average gross income of 1 333.47 USD/year for the owners of the family orchards. Conclusions: Provisioning ecosystem services provided by family orchards seen as an important source of resources, which allow the households of rural communities classified in extreme poverty to cover multiple needs.